(untitled) (Research, Society and Development, 2022)
The objective of the present work was to evaluate the influence of different pasture management strategies in a grassland on the physicochemical characteristics of the soil. For that, a field experiment was carried out, testing overseeding, mowing, use of fire and absence of management in a randomized block design with four replications. A higher level of soil compaction was recorded in the treatments with fire and mowing compared to the absence of management and overseeding. All treatments increased soil organic matter contents, with the greatest variation occurring in the mowing and the smallest in the fire. The H+Al contents increased in all treatments with the greatest variation occurring in the absence of management and the smallest in the mowing and fire. Potassium content decreased only in overseeding and increased more significantly in fire. Phosphorus content increased in overseeding and more significantly in fire. Base saturation decreased in all treatments, more significantly in overseeding and in the absence of management. The results show changes in important parameters for the agricultural use of grassland soil, suggesting that, in general, the use of overseeding and mowing practices present a more favorable change potential than the absence of management or use of fire.